Functional characterization of a novel hexosaminidase, CG7985, in DROSOPHILA eye development - Kıral, Ferdi Rıdvan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
CG7985 is one of the four hexosaminidases encoded by the Drosophila genome. Although the other three hexosaminidases have been well-characterized in terms of their enzymatic activities and metabolic pathways in which they function, CG7985 is the only uncharacterized hexosaminidase in Drosophila. Phylogenetic analysis of CG7985 showed that it differs from the other hexosaminidases grouping together with vertebrate HexDC and C.elegans HEX-2. This sub-branching in the hexosaminidase family comes along with a functional difference. Although the other three hexosaminidases have been shown to cleave N-acetyl-β-D-glucosamine residues, the homologs of CG7985 have been shown to cleave N-acetyl-β-D-galactosamine residues. This slight difference in substrate specificity might result in an important functional difference. Although other hexosaminidases have roles in chitin metabolism and N-Glycan biosynthesis, CG7985 has a presumed role in the ganglioside degradation pathway. We chose the Drosophila eye as a model to functionally characterize CG7985. The expression pattern and protein localization of CG7985 by means of different transgenic lines and a peptide antibody against CG7985 have revealed that it is localized to photoreceptor R7, in the morphogenetic furrow, and the anterior part of the eye imaginal disc. The accumulation of gangliosides due to defective degradation causes a particular type of well-known diseases called lysosomal storage disorders. In these disorders, the storage of waste products in lysosomes often results in enlargement and eventual rupture of lysosomes. This phenomenon, called lysosomal cell death (LCD), triggers apoptosis by a Cathepsin-mediated process. We have shown that the loss-of-function of CG7985 by means of both analysis of mutant and RNAi knockdown resulted in the enlargement of lysosomes. Also, the cells with enlarged lysosomes have been shown to be apoptotic. An unexpected effect of the loss-of-function of CG7985 was the overgrowth of the eye imaginal discs. In an attempt to understand this effect, we have analysed several signalling pathways and have shown that apoptotic cells induce compensatory proliferation in neighboring cells emitting a diffusible growth factor, Wingless.
Keywords: Drosophila.; Drosophila -- Genetics.